2012
DOI: 10.3390/s120404764
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Classifier System for Remote Sensing Image Classification: A Review

Abstract: Over the last two decades, multiple classifier system (MCS) or classifier ensemble has shown great potential to improve the accuracy and reliability of remote sensing image classification. Although there are lots of literatures covering the MCS approaches, there is a lack of a comprehensive literature review which presents an overall architecture of the basic principles and trends behind the design of remote sensing classifier ensemble. Therefore, in order to give a reference point for MCS approaches, this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
143
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(155 citation statements)
references
References 63 publications
2
143
2
1
Order By: Relevance
“…Modifications of the confusion matrix for compatibility with fuzzy classification have been proposed (Binaghi et al, 1999) but studies of fuzzy classification still continue to be published with non-fuzzy evalution (Du et al, 2012). Various indices for representing classification certainty from the class membership vector in each pixel have been proposed (Maselli et al, 1994;Prasad and Arora, 2014), which now allow spatially explicit representation of certainty or graphic visualization independent from position in space.…”
Section: State Of the Artmentioning
confidence: 99%
“…Modifications of the confusion matrix for compatibility with fuzzy classification have been proposed (Binaghi et al, 1999) but studies of fuzzy classification still continue to be published with non-fuzzy evalution (Du et al, 2012). Various indices for representing classification certainty from the class membership vector in each pixel have been proposed (Maselli et al, 1994;Prasad and Arora, 2014), which now allow spatially explicit representation of certainty or graphic visualization independent from position in space.…”
Section: State Of the Artmentioning
confidence: 99%
“…Traditional methods like k-nearest neighbor (k-NN) or maximum likelihood (ML) have been used frequently in the past, but are nowadays increasingly replaced by modern and robust supervised machine learning algorithms including tree-based methods, artificial neural networks or support vector machines. Several studies compared the performance of machine learning algorithms with OBIA or pixel-based classification [31,34,35]. However, it is yet unclear which of the classifiers performs the best with OBIA and pixel-based approaches, especially when used with VHR imagery for detail separation of vegetation components in African savanna.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of majority voting, the output of the ensemble is the most assigned class by classifiers, whereas in the weighted majority voting rule, a weight is assigned to each classifier to favor those classifiers with better performance in the voting decision. Both rules are easily implemented and produce results comparable to more complicated combination schemes [30,36,70]. Moreover, the se rules do not require additional training data because they are not trainable [40] which means that the required parameters for the ensemble are available as the classifiers are generated and their accuracy assessed.…”
Section: Ensemble Classifiersmentioning
confidence: 99%
“…Given the increasing availability of computing resources, various studies have shown that ensemble classifiers outperform individual classifiers [30][31][32]. Yet, the use of ensemble classifiers remains scarce in the context of remote sensing [33] and is limited to image subsets, mono-temporal studies, or to the combination of only a few classifiers [34][35][36].…”
Section: Introductionmentioning
confidence: 99%